A double‐edged sword: The complex interplay between engineered nanoparticles and platelets - Yathreb Asaad; Danielle Nemcovsky‐Amar; Josué Sznitman; Pierre H. Mangin; Netanel Korin (Wiley, 2024)
Abstract Nanoparticles (NP) play a crucial role in nanomedicine, serving as carriers for localized therapeutics to allow for precise drug delivery to specific disease sites and conditions. When injected systemically, NP can directly interact with various blood cell types, most critically with circulating platelets. Hence, the potential activation/inhibition of platelets following NP exposure must be evaluated a priori due to possible debilitating outcomes. In recent years, various studies have helped resolve the physicochemical parameters that influence platelet‐NP interactions, and either emphasize nanoparticles' therapeutic role such as to augment hemostasis or to inhibit thrombus formation, or conversely map their potential undesired side effects upon injection. In the present review, we discuss some of the main effects of several key NP types including polymeric, ceramic, silica, dendrimers and metallic NPs on platelets, with a focus on the physicochemical parameters that can dictate these effects and modulate the therapeutic potential of the NP. Despite the scientific and clinical significance of understanding Platelet‐NP interactions, there is a significant knowledge gap in the field and a critical need for further investigation. Moreover, improved guidelines and research methodologies need to be developed and implemented. Our outlook includes the use of biomimetic in vitro models to investigate these complex interactions under both healthy physiological and disease conditions.